2011
DOI: 10.3122/jabfm.2011.04.100173
|View full text |Cite
|
Sign up to set email alerts
|

Bupropion and Restless Legs Syndrome: A Randomized Controlled Trial

Abstract: Introduction:Restless legs syndrome (RLS) is a common neurological disorder affecting 10% of the population. Most antidepressants exacerbate symptoms; however, correlational studies have noted symptom improvement with bupropion. The purpose of the current study was to examine whether, in a controlled study, bupropion would improve the symptoms of RLS, or at least not exacerbate them.Methods: This was a double-blinded, randomized controlled trial. Twenty-nine participants with moderate to severe RLS received 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 12 publications
1
40
1
Order By: Relevance
“…A higher use of antidepressants in the RLS positive group was recorded in the study by Manconi et al 5 , but no such diff erence was found in the study by Shaygannejad et al 14 . Considering that some antidepressants have the potential of causing RLS 23,24 , while others do not 23,25 , a diff erent medication regimen could explain, at least partly, the above mentioned diff erences among the studies.…”
Section: Discussionmentioning
confidence: 97%
“…A higher use of antidepressants in the RLS positive group was recorded in the study by Manconi et al 5 , but no such diff erence was found in the study by Shaygannejad et al 14 . Considering that some antidepressants have the potential of causing RLS 23,24 , while others do not 23,25 , a diff erent medication regimen could explain, at least partly, the above mentioned diff erences among the studies.…”
Section: Discussionmentioning
confidence: 97%
“…The statistical significance of the improvement of RLS severity score observed in the first 3 weeks of use not remained after 6 weeks, and there were no differences when compared to placebo 98 .…”
Section: Bupropionmentioning
confidence: 93%
“…Treatment of concomitant depression with serotonin selective reuptake inhibitors may exacerbate restless leg symptoms. 6 This study by Bayard et al 7 examines this common problem that affects approximately 10% of our patients. It also addresses the quandary practitioners face when treating concomitant depression with an antidepressant.…”
Section: Restless Legs Syndromementioning
confidence: 99%